2008
DOI: 10.1016/j.neuro.2008.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dietary exposure to food contaminants on the risk of Parkinson's disease

Abstract: This study aimed to investigate the association of Parkinson's disease (PD) with dietary exposure to polychlorinated biphenyls (PCBs) and methylmercury (MeHg) in a community with increased exposure levels. A total of 79 clinically verified idiopathic PD cases and 154 controls matched by sex and age were examined in this case-control study in the Faroe Islands. Blood and hair samples were collected and a questionnaire recorded lifetime information on residence, dietary habits, smoking history, and occupational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(98 citation statements)
references
References 38 publications
2
92
4
Order By: Relevance
“…28 Only 3 studies, all casecontrol, have examined serum organochlorine levels in relation to PD, all with samples collected several years after PD onset. [29][30][31] Two of these found statistically significant increases in odds of PD with higher serum ␤-HCH concentrations, 30,31 whereas the other found a significant association with DDE. 29 In only 1 of these did they report on dieldrin, 31 but all subjects had nondetectable levels.…”
Section: Discussionmentioning
confidence: 98%
“…28 Only 3 studies, all casecontrol, have examined serum organochlorine levels in relation to PD, all with samples collected several years after PD onset. [29][30][31] Two of these found statistically significant increases in odds of PD with higher serum ␤-HCH concentrations, 30,31 whereas the other found a significant association with DDE. 29 In only 1 of these did they report on dieldrin, 31 but all subjects had nondetectable levels.…”
Section: Discussionmentioning
confidence: 98%
“…One casecontrol study observed no associations for intake of zinc, manganese, or copper [492]. A small case-control study (54 cases) reported higher blood levels of mercury in cases than controls [380], a finding not confirmed in another case-control study [313].…”
Section: Mineralsmentioning
confidence: 94%
“…Some studies assessed metal exposure overall through questionnaires without collecting information on occupational history, an approach that also captures recreational metal exposure. Of studies that examined exposure to heavy metals overall, only one reported an increased risk (OR11.84, 95% CI 1.08-130.37) [358], whereas the others found no association [293,313,381]. Another study found no association for residential proximity to steel plants [146].…”
Section: Metalsmentioning
confidence: 99%
See 2 more Smart Citations